REDESAIN LOGO KAMPUNG COKLAT BLITAR SEBAGAI UPAYA PENGEMBANGAN DESTINASI WISATA BERBASIS NATURAL - Atho’illah, Muhammad; Budiardjo, Hardman; Yuan, Dhika (Jurnal Art Nouveau, 2017)
Blok Coklat Village is one of the natural-based tourist destinations that have facilities include; cocoa nurseries, cocoa plantations, cocoa bean dryers, chocolate processing plants, cooking classes, brown outlets, chocolate cafes, meeting rooms, fish therapies and outlets selling chocolate products.Blitar Coklat Village was developed by 48 (forty eight) farmer groups in Blitar district and incorporated as Cooperative named Gapoktan "Guyub Santosa". Blitar Kampung Coklat Plantation is currently growing and frequently visited by local, national and mancanagera tourists.Tourists visiting Kampung Coklat Blitar are given insights on the cultivation of cocoa plants ranging from cocoa plant breeding, ripe cocoa seeding, the drying process of cocoa beans to the processing of cocoa beans into delicious processed chocolate.Based on the results of data analysis, it was found that: first, the Blitar Coklat Village logo does not describe the visual identity as a company characteristic. Second, the logo of Kampung Coklat Blitar has similarities with other company logos. Third, the logo of Kampung Coklat does not describe the vision and mission of the Kampung Coklat company set by the board, which is to build an intelligent, independent, empowered and prosperous Indonesian community.Therefore it is necessary to redesign the logo of Kampung Coklat Blitar which describes the visual identity and vision - the mission of Kampung Coklat as the characteristics of the company, so that in the long term it can improve the image or image of the more developed and advanced Kampong Coklat company, for the development of natural education based tourism, attracting many local, national, even foreign tourists.Keywords: logo redesign, Chocolate Village Identity, Chocolate Village Vision, Corporate Image